2019
DOI: 10.1097/mop.0000000000000794
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of vascular malformation and therapeutic implications

Abstract: Purpose of review Vascular malformations (VaMs) are a consequence of disrupted morphogenesis that may involve arterial, capillary, venous, or lymphatic endothelium alone or in a combination. VaMs can have serious health impacts, leading to life-threatening conditions sometimes. Genetic mutations affecting proliferation, migration, adhesion, differentiation, and survival of endothelial cells, as well as integrity of extracellular matrix are believed to be the pathogenesis of these disorders. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 85 publications
0
37
0
Order By: Relevance
“…The somatic mutation in PI3K/AKT/mTOR signaling pathway discovered in VMs, which is critical to cell growth and proliferation. [ 21 22 ] The new discoveries are the foundation for the treatment of VMs with sirolimus. Positive response with limited toxicity of sirolimus in treatment of VMs were reported in numerous reports,[ 11 23 24 ] but large prospective clinical trials are limited.…”
Section: Discussionmentioning
confidence: 99%
“…The somatic mutation in PI3K/AKT/mTOR signaling pathway discovered in VMs, which is critical to cell growth and proliferation. [ 21 22 ] The new discoveries are the foundation for the treatment of VMs with sirolimus. Positive response with limited toxicity of sirolimus in treatment of VMs were reported in numerous reports,[ 11 23 24 ] but large prospective clinical trials are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of function mutations of RASA1 may therefore lead to activation of RAS and increased downstream signaling via the MEK-ERK1/2 and PI3K-AKT-mTOR pathways that can be potentially targeted. 88 Additional recent studies demonstrated autosomal dominant EPHB4 mutations, named CM-AVM2. 89 This gene encodes a trans-membrane receptor expressed primarily in venous ECs during vascular development interacting with its ligand, EphrinB2, on arterial ECs.…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…1). [3][4][5] A gain-offunction somatic mutation in TEK leads to the overexpression of receptor tyrosine kinase TIE2, which is expressed on venous endothelial cells, resulting in dysplasia of the basement mem-brane and endothelium. While only seen in 25% of sporadic VMs, a somatic mutation in PIK3CA leads to unregulated activation of PI3K, which affects cell proliferation, migration, and survival.…”
Section: Pathogenesis and Clinical Presentationmentioning
confidence: 99%